Cyclic Educational Transitions and Social Inequality: Re-applications After Educational Rejections - Heiskala Laura; Kilpi-Jakonen Elina; Sirniö Outi; Erola jani (Turun yliopisto, 2026)
Educational transitions are cyclic processes in which re-applications are an essential but understated part of access. We study social inequalities in re-application behavior to identify the extent to which educational intentions are more constrained among students from the lower social strata. We explore applications to universities in Finland, where student selection takes place at the gates of the institutions. With full population register data and discrete-time event-history models, we show how parental education, previous national examination grades and various life-course changes after the rejection, such as entering the labor market and having children, are associated with re-applications. Net of other differences, children of university-educated parents have a 6 percentage points lower probability to stop applying to university after being rejected compared to their counterparts with lower educated parents. We argue that ability-based intake to educational institutions, which is seen to be meritocratic, is not sufficient for reducing social inequalities if staying in the queue is socially selective.